Kontrol Guru Pendidikan Agama Islam Mengatasi Perilaku Penyimpangan Akhlak Siswa Di SMP Negeri Muara Beliti - Arikarani, Yesi; Yanti, Hamida Juni; ngimadudin, Ngimadudin; Mukmin, Taufik (Edification Journal : Pendidikan Agama Islam, 2023)
Today's youth associations are very worrying due to the development of modernization currents and the depletion of one's morals and faith. Moral impoverishment as a contributing factor to the occurrence of deviant behavior. This research is to deal with the problem of school deviant behavior by directing the integration of the formulation of social aspects subject matter with Islamic religious education. This research uses qualitative research methods (field research), data collection techniques, data analysis techniques and triangulation. The findings of this study that the control of Islamic religious education teachers on the behavior of deviant morals of students at the first Muara Beliti State Junior High School, teachers provide solutions in the form of advice, motivation, religious habituation such as carrying out zuhur congregational prayers, listening to lectures and kultums. Second, efforts to prevent teachers in overcoming problems through repressive and curative prevention. Third. Factors that cause the behavior of student moral storage are family, school, and community. Play an important role in realizing good behavior based on the role of parents, teachers, and the community.